205k views
2 votes
6x-3y=6 y=2x+5 USE SUBSTITUTION SHOW YOUR WORK

User Dikkini
by
8.1k points

2 Answers

6 votes
6x - 3y = 6 ⇒ 6x - 3y = 6 ⇒ 6x - 3y = 5
y = 2x + 5 ⇒ 2x - 1y = 5 ⇒ 6x - 3y = 15
-6y = -10
-6 -6
y = 1 2/3
6x - 3(1 2/3) = 6
6x - 5 = 6
+5 +5
6x = 1
6 6
x = 1/6
(x, y) = (1/6, 1 2/3)
User Renatopp
by
7.7k points
5 votes
What you're going to do is plug in y=2x+5 into the 3y ( getting rid of the y to solve for x only) so that gives you...... 6x-3(2x+5)=6. Next, you're going to multiply -3 to 2x and 5. Now it gives you..... 6x-6x-15=6. The x's cancel out leaving the equation with -15=6 making it an Inconsistent system also known as a No Solution system. 
User Llamageddon
by
8.4k points